Comparing the rate of weapon and ornament diversification - MEGAN WATTS (2022)
In some species in one sex, generally males, ornaments evolve to attract females and/or sexually selected weapons evolve as a response to intrasexual competition for mating opportunities. A key prediction of classic Darwin/Fisher/Lande sexual selection theory is that sexually selected ornaments should evolve faster than sexually selected weapons. As male ornaments and female preferences for particular ornamental traits coevolve, selection occurs in both males and females and a positive feedback loop potentially enhancing the rate of trait evolution can develop under the Fisher process (Fisherian runaway selection)In this thesis I measure the rate of trait evolution of many examples of weapons and ornaments to test this at a macroevolutionary scale. . I assembled data on weapon and ornament traits from 22 diverse animal taxa. Pairs of weapon and ornament datasets comprising closely related taxa were formed to control factors such as generation time that may influence the different rates between traits. Trait values were standardised and the rates were compared using recently developed phylogenetic analyses under both Brownian motion and Ornstein-Uhlenbeck evolutionary models. I found strong evidence under both models that ornaments have consistently evolved faster than weapons. This suggests that Fisherian runaway processes have broad influence on the evolution of sexually selected ornaments at macroevolutionary scales across diverse taxa.